(untitled) (Uzbek Scholar Journal, 2024)
This article discusses the use of mathematical knowledge and the laws of physics in teaching astronomy. So, since the integration of subjects is one of the directions in the search for new pedagogical solutions related to the unification of individual sections of different disciplines into a single whole in order, firstly, to overcome the uniformity of goals and functions of teaching; secondly, to create in students a holistic idea of their future profession (integration here represents the goal of learning) and to provide a common space for the convergence of subject knowledge (integration here represents the means of learning). An example of the use of mathematical knowledge in the study of astronomy is given. Thus, one of the forms of attracting students to independent creative activity is to perform computational work that allows them to deepen theoretical knowledge and apply it to solve practical problems. This teaching method contributes to the achievement of the following goal: it forms in students the necessary system of knowledge and skills and ensures a high level of self-development, as well as development for self-learning. Interdisciplinary integration has successfully contributed to increasing the theoretical and practical knowledge of university students, within the framework of which, on the basis of cognitive activity, opportunities are created for the formation of the competitiveness of young people.